Determination of Behavioral Pain Responses During Invasive Nursing Interventions in Unconscious Patients - Hussien Salman, Zineb; Abdullah Athbi, Hassan (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Pain assessment is the first and the most important step in nursing management and has a direct effect on patient’s outcomes. Unconscious patients are often unable to communicate, which make difficulties in pain assessment and management. This study aims to investigate the effect of selected invasive nursing interventions on behavioral pain responses in unconscious patients. A cross-sectional observational study was carried out from 26th September 2024, to 28th May 2025, in the intensive care units at Imam Al-Hussein Medical City and Imam Al-Hassan Al-Mujtaba Teaching Hospital in Holy Kerbala City. A purposive sample consist of 80 unconscious intubated critically ill patients .The data were analyzed using the IBM Statistical Package of Social Sciences Version 26. Results: The results revealed sever to moderate degree of pain during procedures, mainly endotracheal suctioning (the mean BPS score: 8.7 ± 1.7), with more than one-half (52.5%) of patients suffering from moderate pain and 37.5% from severe pain. Conclusion: During their stay in the intensive care unit, the unconscious patients on mechanical ventilation were silently experiencing a comparatively high amount of discomfort (p-value= 0.000) during all three procedures.